Efek Fotolistrik dan Aplikasinya Dalam Teknologi Surya - Hartanti, Maya; Amilian, Dina (Lembaga Publikasi Ilmiah Nusantara, 2025)
The photoelectric effect is a physical phenomenon in which electrons are emitted from a metal surface as a result of exposure to light of a specific frequency. This phenomenon not only challenged the paradigms of classical physics but also laid the foundation for the development of modern technology, particularly in the field of renewable energy. This article provides a comprehensive discussion of the fundamental principles of the photoelectric effect, beginning with the quantum theory of light and moving to the classical experiments conducted by Albert Einstein, which refined our understanding of the dual nature of light. The primary focus of this study is to explore the application of the photoelectric effect in solar technology, particularly in the design and efficiency of next-generation solar cells. Photovoltaic technology utilizes this effect to directly convert light energy into electrical energy. Additionally, the article highlights recent innovations in semiconductor materials and nanostructures that enhance the performance of solar devices. Recent data show that the use of materials such as perovskite and multi-junction silicon can significantly improve energy conversion efficiency. The analysis was conducted using a qualitative approach based on a review of the latest literature from various scientific journals. The findings indicate that a deep understanding of the photoelectric effect is crucial for the development of sustainable, efficient, and environmentally friendly solar technologies. Thus, the integration of fundamental physics with technological innovation can drive the advancement of clean energy for the future.